2014
DOI: 10.1002/pssr.201409087
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of arc deposited magnetic (Cr,Mn)2AlC MAX phase films

Abstract: (Cr1–xMnx)2AlC MAX phase thin films were synthesized by cathodic arc deposition. Scanning transmission electron microscopy including local energy dispersive X‐ray spectroscopy analysis of the as‐deposited films reveals a Mn incorporation of as much as 10 at% in the structure, corresponding to x = 0.2. Magnetic properties were characterized with vibrating sample magnetometry, revealing a magnetic response up to at least room temperature. We thus verify previous theoretical predictions of an antiferromagnetic or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 9 publications
4
78
2
Order By: Relevance
“…Cr and Mn depends heavily on the A element. Also known is that the highest observed transition temperature is observed for A = Al in [31].…”
Section: B Effect Of M a And X Elements On Magnetic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cr and Mn depends heavily on the A element. Also known is that the highest observed transition temperature is observed for A = Al in [31].…”
Section: B Effect Of M a And X Elements On Magnetic Propertiesmentioning
confidence: 99%
“…These results were seen as an important step towards the (Cr 0.5 Mn 0.5 ) 2 AlC composition, predicted to be ferromagnetic, by Dahlqvist et al [7]. Magnetic properties of this phase were not studied at the time, this was instead done for subsequently synthesized arc deposited films [31] found to have a composition of (Cr 0.8 Mn 0.2 ) 2 AlC, stating this the highest Mn concentration in an Al based MAX phase to date. Magnetic characterization revealed a significant magnetic signal up to and including room temperature with virtually no change in magnetization from 5 up to 280 K, indicating a very high transition temperature compared to other studied magnetic MAX phases.…”
Section: Thin Film Synthesismentioning
confidence: 99%
“…In 2013, three different magnetic MAX phases obtained through alloying between Cr and Mn on the M site were presented: (Cr 1Àx ,Mn x ) 2 GeC (x $ 0.25) by Ingason et al, 8 Cr 1Àx ,Mn x GaC (where 0 < x < 0.5) by Lin et al, 9 and (Cr 1Àx ,Mn x ) 2 AlC (x $ 0.16) by Mockute et al 10,11 These findings were followed by even more recent reports on these alloys. [12][13][14] Later, Ingason et al proceeded to synthesize Mn 2 GaC, 15 the first MAX phase with a hitherto unexplored M site element, Mn, since Nowotny's pioneering work.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Later, Ingason et al proceeded to synthesize Mn 2 GaC, 15 the first MAX phase with a hitherto unexplored M site element, Mn, since Nowotny's pioneering work. In the case of (Cr 1Àx ,Mn x ) 2 AlC, 10,11 (Cr 1Àx ,Mn x ) 2 GeC, 8 and Mn 2 GaC, 15 the successful thin film synthesis was prompted by predictions of thermodynamic phase stability based on a first-principles approach developed by Dahlqvist et al 16,17 In this work, we investigate selected physical properties of Mn 2 GaC, which, due to its recent discovery, is still largely unexplored. The electronic, vibrational, and elastic properties are calculated from first principles, including an evaluation of the effect of different magnetic spin configurations of Mn 2 GaC.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Recently, it has been demonstrated that magnetic order can be changed and stabilized up to room temperature by substituting Cr by Mn. [9,[11][12][13][14][15][16] Stable (Cr 1−x Mn x ) 2 AC (A = Al, Ge or Ga) type MAX phase compounds can be considered as a new family of magnetic MAX phases, which exhibit FM properties. Furthermore, the Mn 2 GaC magnetic compound has been synthesized as a heteroepitaxial thin film containing Mn as the exclusive M element.…”
mentioning
confidence: 99%